Caloric restriction prevents obesity- and intermittent hypoxia-induced cardiac remodeling in leptin-deficient ob/ob mice - Jones, Aaron A.; Framnes-DeBoer, Sarah N.; Shipp, Arianne; Arble, Deanna M. (Frontiers in Physiology, 2022)
Background: Intermittent hypoxia (IH), a key characteristic of obstructive sleep apnea, is independently associated with cardiometabolic impairment. While endogenous leptin levels may provide cardioprotective effects against hypoxia, leptin resistance is common among obese individuals presenting with obstructive sleep apnea. Methods: Here, we assessed left ventricle (LV) function using M-mode echocardiography in lean wild-type, calorically-restricted ob/ob, and obese ob/ob mice before and after 6 days of IH to determine how obesity and intermittent hypoxia interact to affect cardiac function independent of leptin signaling. Results: Calorically-restricting ob/ob mice for 4 weeks prior to IH exposure prevented weight gain (-2.1 ± 1.4 g) compared to free-fed ob/ob mice (8.7 ± 1.1 g). Free-fed ob/ob mice exhibited increased LV mass (0.713 ± 0.008 g) relative to wild-type mice (0.685 ± 0.004 g) and increased posterior wall thickness (0.089 ± 0.006 cm) relative to calorically-restricted ob/ob mice (0.072 ± 0.004 cm). Following 6 days of IH, free-fed ob/ob mice exhibited increases in cardiac output (44.81 ± 2.97 pre-IH vs. 57.14 ± 3.09 ml/min post-IH), LV diameter (0.400 ± 0.007 pre-IH vs. 0.428 ± 0.009 cm post-IH) and end diastolic volume (0.160 ± 0.007 pre-IH vs. 0.195 ± 0.012 ml post-IH) that were not detected in wild-type or calorically-restricted ob/ob mice. Conclusion: Caloric restriction can prevent obesity-induced LV hypertrophy and protect against acute IH-induced cardiac remodeling independent of leptin signaling. These findings may have clinical implications for obstructive sleep apnea.